Analisis Jatuh Tegangan Pada Penyulang 20 kV Berdasarkan pada Perubahan Beban (Studi Kasus Penyulang Penfui dan Penyulang Oebobo PT. PLN Persero Rayon Kupang) - Sampeallo, Agusthinus S. (Universitas Nusa Cendana, 2013)
Steady voltage on the feeder depends on the line impedance and load pattern. The second major parameter that causes the voltage drop to the line, where the greater the value of line impedance and load the greater the voltage drop occurs. The purpose of this study was to examine the influence of load changes on the magnitude of the voltage drop occurs in the primary line distribution. Case studies conducted on two feeders that Penfui and Oebufu feeders at PT. PLN (Persero) Kupang. The obtained than due to the voltage drop on Penfui feeders results impedance, of the 2.9531% and at Oebufu feeders of the 4.9632%. Meanwhile, when loaded to the maximum voltage drop at Penfui feeders in the amount of 2.5447% and Oebufu feeders in the amount of 4.1068%. When analyzed at the time of loading per-phase the voltage drop obtained is on Penfui feeders, phase R of the 3.1161%, phase S of the 3.0616% and phase T of the 3.0597%. And than value drop voltage to Oebufu feeders, phase R of the 4.776%, phase S of the 4.18 16 % and for phase T of the 4.1737 %.